PERANCANGAN SISTEM INFORMASI KEHADIRAN PEGAWAI DAN SKP (SIKAP) PADA INSTITUT AGAMA ISLAM NEGERI (IAIN) METRO - Toto Andri Puspito (Jurnal informasi dan komputer, 2022)
In early 2020, the world was shocked by the outbreak of a new pneumonia named coronavirus disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The spread of this disease has had a wide social and economic impact. During the spread of the COVID-19 pandemic, many things must be done to avoid the spread of the virus, namely by maintaining cleanliness and doing physical distancing. This also has an impact on the world of education, in this case universities, in carrying out their activities to monitor employee performance, use attendance that uses fingerprint technology. Attendance using fingerprints during a pandemic can endanger employee health because transmission can occur when the fingerprint machine is touched alternately by employees. The development of internet/online technology is a way that can reduce direct interaction between humans by building an employee attendance information system and SKP that can be accessed by employees in campus area locations with campus network connections using their respective Android or IOS devices. Data collection methods used in this study were interviews and documentation. The System Development method used is the Research and Development method with the Waterfall approach which is systematic, sequential in building software. With this system, employee performance can be monitored properly and employees can still maintain their respective health during the pandemic, which requires working by implementing physical distancing.